Tumor-associated CD3- and CD8-positive immune cells in colorectal cancer: The additional prognostic value of CD8+-to-CD3+ ratio remains debatable - Kasurinen Jussi; Hagström Jaana; Kaprio Tuomas; Beilmann-Lehtonen Ines; Haglund Caj; Böckelman Camilla (IOS Press BV, 2022)
Background
A large number of infiltrating CD3- and CD8-positive inflammatory cells indicates an improved survival in colorectal cancer (CRC), similar to many other cancers.
Objective
We investigated the prognostic value of different combinations of CD3- and CD8-positive immune cells in CRC patients.
Methods
The densities of CD3- and CD8-positive cells in intratumoral and stromal tissues were evaluated from 539 patients, for which we calculated a CD3 tumor–stroma index, a CD8 tumor–stroma index, and a CD3–CD8 tumor–stroma index.
Results
High CD3 and CD8 tumor–stroma indices associated with stage I to II disease (p < 0.001 for both). The CD3 tumor–stroma index associated with a colonic tumor location (p = 0.006), while the CD8 tumor–stroma index associated with right-sided tumors (p < 0.001) and histological grade 3 tumors (p = 0.032). High intratumoral and stromal densities for CD3- and CD8-positive immune cells, the CD3 tumor–stroma index, the CD8 tumor–stroma index, and the CD3–CD8 tumor–stroma index all indicated a better DSS.
Conclusions
The CD3 tumor–stroma index carries a strong prognostic value in CRC, and none of the CD3 and CD8 combinations we analyzed proved superior.